Final answer:
The equivalent representation of the given sequence is a_n = (-1)^n * (n + 1).
Step-by-step explanation:
The given sequence is defined recursively as follows:
a1 = 3
an = an-1 - 4 + an-2
To find an equivalent representation, we can start with the first few terms and look for a pattern. The given sequence can be rewritten as:
a1 = 3
a2 = 3 + (-4) + 3 = 2
a3 = 2 + (-4) + 3 = 1
a4 = 1 + (-4) + 2 = -1
a5 = -1 + (-4) + 1 = -4
a6 = -4 + (-4) + (-1) = -9
Based on this pattern, we can conclude that the equivalent representation of the given sequence is:
an = (-1)^n * (n + 1), n ≥ 1